2018
DOI: 10.3892/ijmm.2018.3410
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase-4 and histone deacetylase-8 regulate interleukin-1β-induced cartilage catabolic degradation through MAPK/JNK and ERK pathways

Abstract: Interleukin-1β (IL-1β)-induced inflammatory response is associated with osteoarthritis (OA) and its development. Histone deacetylase (HDAC) may be involved in regulating this pathogenesis, but the mechanism has yet to be elucidated. The aim of the present study was to investigate the mechanism underlying the regulation of IL-1β-stimulated catabolic degradation of cartilage by HDAC. An in vitro model of OA was generated using rat articular chondrocytes (rACs) treated with IL-1β. The role of HDAC in IL-1β-induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 72 publications
1
32
0
Order By: Relevance
“…The MAPK signaling pathway, which is a group of serine/threonine protein kinases involved in the cellular signal transduction [60], which regulated many cellular functions, affects a large number of human diseases. Previous studies have demonstrated the effect of MAPK signals on tumor metastasis [61,62], osteogenesis [63,64], osteoarthritis [65,66], or certain inflammatory diseases [67]. For example, it can regulate the proliferation and differentiation of brain cells [68].…”
Section: Discussionmentioning
confidence: 99%
“…The MAPK signaling pathway, which is a group of serine/threonine protein kinases involved in the cellular signal transduction [60], which regulated many cellular functions, affects a large number of human diseases. Previous studies have demonstrated the effect of MAPK signals on tumor metastasis [61,62], osteogenesis [63,64], osteoarthritis [65,66], or certain inflammatory diseases [67]. For example, it can regulate the proliferation and differentiation of brain cells [68].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it also had a better reversal effect than PDTC, i.e., on the negative effect of TNF-α-induced autophagy inhibition and apoptosis activation. Previous studies reported that in addition to the NF-κB signaling pathway, other signaling pathways such as the MAPK/JNK and ERK pathways are also involved in the pathogenesis process of OA ( Wang et al, 2018 ). In the future experiments, we would like to verify whether icariin protects against OA via these or other signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…With the rapid aging of global population, the incidence rate of OA has increased in recent years, and the morbidity is > 10%. [4,18]. OA is a chronic progressive joint disease, characterized by arthrosynovitis, degeneration and destruction of cartilage, subchondral bone sclerosis, and osteophyte formation [19].…”
Section: Discussionmentioning
confidence: 99%
“…OA is a common orthopedic disease among the elderly and a chronic, in ammation-related progressive degenerative disease characterized by destruction of cartilage and aggrecan degradation of cartilage extracellular matrix (ECM), which is affected by many risk factors, such as gender, age, obesity, in ammation, and trauma [2,3]. Although the pathogenesis of OA remains to be elucidated, it is speculated that the imbalance between anabolism and catabolism in cartilage ECM contributes to the progression of OA [1,4]. Previous researchers have shown that collagens and aggrecan are the key components of cartilage ECM [5].…”
Section: Introductionmentioning
confidence: 99%